Clinically important factors influencing the diagnostic measurement of pleural fluid pH and glucose. - Rahman, N; Mishra, E; Davies, H; Davies, R; Lee, Y (2008)
RATIONALE: Accurate pleural fluid pH and glucose measurement is a key component in the diagnosis and management of patients with pleural effusion. Standardized methods of pleural fluid collection have not been defined. OBJECTIVES: To assess the effect of common clinical factors that may distort measurement accuracy of pleural fluid pH and glucose. METHODS: Ninety-two exudative pleural aspirates were collected in commercially available blood gas syringes. MEASUREMENTS AND MAIN RESULTS: Samples were analyzed immediately using a blood gas analyzer. The effects of residual air, lidocaine, heparin, and delay in analysis (24 h) on pH and glucose measurement accuracy were assessed. Pleural fluid pH was significantly increased by residual air (mean +/- SD, 0.08 +/- 0.07; 95% confidence interval [CI], 0.06 to 0.09; P < 0.001) and significantly decreased by residual lidocaine (0.2 ml; mean change in pH, -0.15 +/- 0.09; 95% CI, -0.13 to -0.18; P < 0.001) and residual heparin (mean change in pH, -0.02 +/- 0.05; 95% CI, -0.01 to -0.04; P = 0.027). Pleural fluid pH was stable at room temperature for 1 hour and significantly increased at 4 (mean +/- SD, 0.03 +/- 0.07; 95% CI, 0.01 to 0.04; P = 0.003) and 24 hours (0.05 +/- 0.12; 95% CI, 0.03 to 0.08; P < 0.001). Pleural fluid glucose concentration was not clinically significantly altered by residual air, lidocaine (up to 0.4 ml), or 24-hour analysis delay. CONCLUSIONS: Accuracy of measured pleural pH is critically dependent on sample collection method. Residual air, lidocaine, and analysis delay significantly alter pH and may impact on clinical management. Pleural fluid glucose concentration is not significantly influenced by these factors. Protocols defining appropriate sampling and analysis methods are needed.